Solutions To Differences In Sentences For Parallel Integration Of Restorative Justice In Indonesian Courts - Handar Subhandi Bakhtiar; Amriyanto Amriyanto; Samsu Alam Maddussila (Jurnal Hukum dan Peradilan, 2023)
This study describes the problems and solutions related to differentiating sentences for the parallel integration of restorative justice in Indonesian courts. This study is normative-legal research using statute, comparative, and conceptual approaches. This study utilizes primary legal materials and secondary legal materials. This study is based on 25 (twenty-five) cases decided by judges in Indonesian courts. The research results indicate that the values of restorative justice are very relevant to the cultural values of gotong royong in Indonesia. Judges must consider the community’s cultural values and the implementation of restorative justice in their decisions. Parallel integration of justice has been re-applied in Indonesian courts. Still, in practice, judges do not have guidelines for parallel integration, so it is very possible that there will be differences in punishment for applying parallel integration. Therefore, as a solution to the problem of differentiation of sentences, the authors propose 2 (two) concepts of court decisions, namely (1) the verdict of the indictment cannot be accepted, and (2) the decision of the public prosecutor cannot be accepted.